Catching the feeling of flying: cultivating Olympic trampoline champions - Petersen, B.; Seanor, M.; Schinke, R. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
Olympic podium performances represent peak accomplishments for an athlete and his/her team. As such, researchers seek to understand the pathway to the Olympic podium and produce athlete development models capable of helping athletes reach these achievements. The Environmental Success Factors model (ESF; Henriksen et al., 2010), an emergent athlete development framework, shifts focus away from the importance of social agents in isolation (e.g., coaches, teammates) to the importance of a holistic environmental development context. The ESF model demonstrates how contextual inputs (i.e., preconditions, processes) shape the sport environment`s culture and athletes` subsequent performance outcomes. Using this framework, we conducted an intrinsic case study to explore the athlete development program at Skyriders Training Environment (STE), a Canadian trampoline training facility sporting consistent Olympic medal performances across five previous Olympic cycles. Participants led a researcher on guided walks (a mobilemethod of conversational interviews), contextualizing the sport environment and discussing environmental factors (e.g., coaching, facility) that interdependently contribute to their consistent success, prompted by relevant cues throughout the facility. Consequently, we constructed an ESF model of STE`s athlete development program. An interpretive thematic analysis identified three main themes discussing (a) creating lift (i.e., creating an environment of success), (b) providing a tailwind (i.e., establishing partnerships), and (c) soaring onto the Olympic podium (i.e., training for excellence). Unearthing the idiosyncrasies of this unique training environment provides insight into the "how to" of elite athlete development. These findings can be translated into other sport contexts and aid practitioners in building a holistic development program.